Byron J. Good: Medicine, Rationality, and Experience: An Anthropological Perspective - Hansen, Helle Ploug (Tidsskriftet Antropologi, 1994)
Byron J. Good: Medicine, Rationality, and Experience: An Anthropological Perspective Anmeldes af Helle Ploug Hansen